Model criterion and basic principles of construction bank data abrasive materials durability - Вишневський, О.А. (Proceedings of National Aviation University (archive), 2006)
The generalized model is created and the criterion of an abrasive wear of surfaces of materials is determined at not hard-mounted corpuscles. The principle of construction of a data bank of an abrasive wear resistance of materials of friction units is determined.